Powerful Radio Sources in the Southern Sky. I. Optical Identifications - Massaro, F. (2023)
Since the early sixties, our view of radio galaxies and quasars has been drastically shaped by discoveries made thanks to observations of radio sources listed in the Third Cambridge Catalog and its revised version (3CR). However, the largest fraction of data collected to date on 3CR sources was performed with relatively old instruments, rarely repeated and/or updated. Importantly, the 3CR contains only objects located in the Northern Hemisphere, thus having limited access to new and innovative astronomical facilities. To mitigate these limitations, we present a new catalog of powerful radio sources visible from the Southern Hemisphere, extracted from the GLEAM 4 Jy (G4Jy) catalog and based on equivalent selection criteria as the 3CR. This new catalog, named G4Jy-3CRE, where the E stands for “equivalent,” lists a total of 264 sources at decl. below −5° and with 9 Jy limiting sensitivity at ∼178 MHz. We explored archival radio maps obtained with different surveys and compared them with optical images available in the Pan-STARRS, DES, and DSS databases to search for optical counterparts of their radio cores. We compared mid-infrared counterparts, originally associated in the G4Jy, with the optical ones identified here, and we present results of a vast literature search carried out to collect redshift estimates for all G4Jy-3CRE sources resulting in a total of 145 reliable z measurements.